Deficits in auditory frequency discrimination and speech recognition in cochlear implant users. (March 2015) - Turgeon, Christine; Champoux, François; Lepore, Franco; Ellemberg, Dave
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives Speech recognition varies considerably following cochlear implantation for reasons that are still poorly understood. Considering the role of frequency discrimination in normal speech recognition, the aim of this study was to investigate the association between deficits in auditory frequency discrimination and speech recognition in cochlear implant users. Methods Frequency discrimination thresholds and speech recognition were assessed in a group of 20 cochlear implant users and 16 normally hearing controls. Results Based on their results on the speech recognition task, the cochlear implant users were categorized either as proficient (n = 10) or non-proficient users (n = 10). The non-proficient cochlear implant users had poorer auditory frequency discrimination compared to the normal hearing participants and proficient cochlear implant users (both P < 0.05). No significant difference was found between the proficient cochlear implant users and the normally hearing group (P > 0.05). Furthermore, a bivariate correlation analysis revealed a relationship between speech recognition and frequency discrimination. Conclusions The present findings suggest an association between auditory frequency discrimination and speech recognition proficiency in cochlear implant users. Although no causal link can be drawn from these data, possible reasons for this association are discussed.